The Relationship Between Familial Mediterranean Fever Gene (MEFV) Mutations and Clinical and Radiologic Parameters in Multiple Sclerosis Patients - Terzi, M.; Taşkin, E.; Ünal Akdemir, N.; Baǧci, H.; Onar, M. (Informa Healthcare, 2015)
Objective: Central nervous system (CNS) involvement in patients with familial Mediterranean fever (FMF) is considerably rare. Patients with FMF may exhibit clinical and radiologic symptoms similar to multiple sclerosis (MS). However, the impact of the Familial Mediterranean Fever Gene (MEFV) mutations on the clinical course of MS is not fully understood as yet.Methods: In our study, we investigated the presence of probable MEFV mutations in patients diagnosed with definite MS and the association of these mutations with the clinical course, radiologic characteristics and disability status of the individuals. A total of 105 patients diagnosed with definite MS according to the McDonald criteria and a control group of 112 non-symptomatic individuals were included in the study.Results: Thirty-seven patients (35.2%) had MEFV gene mutations; three were compound heterozygotes (M694V/E148Q; M694V/V726A; P369S/E148Q) and one was homozygous for P369S. No statistically significant differences were found among patients with MS and healthy individuals with respect to existing mutations. In addition, we did not observe a statistically significant relationship between MEFV mutations and the gender of the patients, oligoclonal band (OCB) positivity, Expanded Disability Status Scale (EDSS), disease onset age, clinical presentation, affected neurologic systems, existence of spinal lesions, response to immunomodulatory treatment, time to reach EDSS scores of 3 and 6, the number of attacks and the average number of lesions on a brain MRI.Conclusion: Our results indicate that MEFV gene mutations do not affect the neurologic prognosis in patients with MS. However, additional research studies involving more patients with MS and clinical forms are warranted to confirm our results. © 2014 Informa Healthcare USA, Inc.
Keywords: Familial Mediterranean Fever; Multiple Sclerosis; Prognosis